Vulnerability, Embedded Agency, and Downward Social Mobility of Young Asylum Seekers - Gabrielli, Mara (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2023)
From an intersectional perspective, the situational and inherent vulnerability faced by two young asylum seekers in Catalonia, Spain, were analyzed through case studies that illustrate how these young people navigated within unpredictable and changing environments that hampered their embedded agency. Their settlement as social navigation highlights the temporal dimensions of the migration process. Waiting was also a key element that marked and regulated their settlement from a normative, relational, and existential dimension. The results highlight downward social mobility and precarious integration into the host society due to institutional, structural, and socio-cultural constraints.